E-commerce today and tomorrow: A truly generalized and active framework for the definition of electronic - Poong, , Yewsiang; Zaman, , Khaliq-Ul; Talha, , Mohammad (2006)
E-commerce can be viewed from different perspectives by different people. Existing e-commerce frameworks consist of rigid and specific fundamental components of e-commerce. E-commerce field is constantly facing new challenges and new situations. To deal with these challenges, an Active E-commerce Framework is being proposed. This framework consists of six important e-commerce components each composed of several instances. The components and instances of the framework are subject to the rule of Component Flexibility (CF) and Instance Flexibility (IF) respectively. The user perspective is considered as the most important and vital component in this model. By using the user perspective component as the guiding ground, different e-commerce definitions can be constructed. This paper aims at providing an e-commerce framework that can cater for different views of e-commerce as well as assist a person in constructing e-commerce definition from his own perspective.